Antecedents of academic actual help-seeking behaviour and support services utilisation among distance education students - Somuah, Beatrice Asante; Ahiatrogah, Paul Dela; Segbenya, Moses; Bervell, Brandford (Frontiers in Psychology, 2024)
The purpose of the study was to unravel the determinants that necessitate academic help-seeking intentions and promote the utilization of support services among distance education students. This study adopted a quantitative approach based on cross-sectional survey design. The target population of the study comprised all distance education students of the College of Distance Education, University of Cape Coast. A multi-stage sampling procedure was used to select a sample of 290 respondents for the study. The main data collection instrument was a questionnaire and the data was collected from June to December, 2023. Descriptive statistics (mean and standard deviation) were used to analyse preliminary data, while the main data was analysed by structural equation modelling technique. The study found that social support, subjective needs, and availability of help were the antecedents of actual academic help-seeking behaviour among distance learners. Depressive needs were not considered as an antecedent of help-seeking behaviour. Thus, social support, subjective needs, and availability of help were significantly related to actual help-seeking behaviour among distance learners. The study further found that actual help-seeking behaviour among distance learners was also significantly related to the actual use of support services available to these learners. Finally, actual help-seeking behaviour among distance learners significantly mediated the relationship between social support, subjective needs, availability of help, and actual use of support services available to distance students. It was therefore recommended that authorities of distance education should make support services available to distance learners online and in-person to be able to meet the needs of different categories of students as well as the provisions of platforms for building social support systems among distance learners.